Investigation of neural progenitor cell induced angiogenesis after embolic stroke in rat using MRI - Jiang, Quan; Zhang, Zheng Gang; Ding, Guang Liang; Zhang, Li; Ewing, James R.; Wang, Lei; Zhang, RuiLan; Li, Lian; Lu, Mei; Meng, He; Arbab, Ali S.; Hu, Jiani; et al. (NeuroImage (Orlando, Fla.), 2005)
Using MRI, we investigated dynamic changes of brain angiogenesis after neural progenitor cell transplantation in the living adult rat subjected to embolic stroke. Neural progenitor cells isolated from the subventricular zone (SVZ) of the adult rat were labeled by superparamagnetic particles and intracisternally transplanted into the adult rat 48 h after stroke ( n = 8). Before and after the transplantation, an array of MRI parameters were measured, including high resolution 3D MRI and quantitative T 1, T 1sat ( T 1 in the presence of an off-resonance irradiation of the macromolecules of brain), T 2, the inverse of the apparent forward transfer rate for magnetization transfer ( k inv), cerebral blood flow (CBF), cerebral blood volume (CBV), and blood-to-brain transfer constant ( K i) of Gd-DTPA. The von Willerbrand factor (vWF) immunoreactive images of coronal sections obtained at 6 weeks after cell transplantation were used to analyze vWF immunoreactive vessels. MRI measurements revealed that grafted neural progenitor cells selectively migrated towards the ischemic boundary regions. In the ischemic boundary regions, angiogenesis confirmed by an increase in vascular density and the appearance of large thin wall mother vessels was coincident with increases of CBF and CBV (CBF, P < 0.01; CBV, P < 0.01) at 6 weeks after treatment, and coincident with transient increases of K i with a peak at 2 to 3 weeks after cell therapy. Relative T 1, T 1sat, T 2, and k inv decreased in the ischemic boundary regions with angiogenesis compared to that in the non-angiogenic ischemic region ( T 1, P < 0.01 at 6 weeks; T 1sat, P < 0.05 at 2 to 6 weeks; T 2, P < 0.05 at 3 to 6 weeks; k inv P < 0.05 at 6 weeks). Of these methods, K i appear to be the most useful MR measurements which identify and predict the location and area of angiogenesis. CBF, CBV, T 1sat, T 1, T 2, and k inv provide complementary information to characterize ischemic tissue with and without angiogenesis. Our data suggest that select MRI parameters can identify the cerebral tissue destined to undergo angiogenesis after treatment of embolic stroke with cell therapy.